Evaluation of Adherence, Hydrophobicity, Aggregation, and Biofilm Development of Flavobacterium johnsoniae-Like Isolates - Basson, A.; Flemming, L. A.; Chenia, H. Y. (Microbial ecology, 2008)
Flavobacterium spp. isolates have been identified in diverse biofilm structures, but the mechanism of adherence has not been elucidated. The absence of conventional biofilm-associated structures such as fimbriae, pili, and flagella suggest that surface hydrophobicity, and/or autoaggregation and coaggregation may play an important role in adherence and biofilm formation. The biofilm-forming capacity of 29 Flavobacterium johnsoniae-like isolates obtained from South African aquaculture systems was assessed using microtiter plate assays. The role of hydrophobicity [salting aggregation test (SAT) and bacterial adherence to hydrocarbons (BATH) assays], autoaggregation, and coaggregation on biofilm formation by Flavobacterium spp. was also investigated, while biofilm structure was examined using flow cells and microscopy. All isolates displayed a hydrophilic nature, but showed varying levels of adherence in microtiter assays. Significant negative correlations were observed between adherence and biofilm-forming capacity in nutrient-poor medium at 26°C and BATH hydrophobicity and motility, respectively. Isolates displayed strain-to-strain variation in their autoaggregation indices and their abilities to coaggregate with various Gram-negative and Gram-positive organisms. Microcolony and/or biofilm development were observed microscopically, and flavobacterial isolates displayed stronger biofilm structures and interaction with a Vibrio spp. isolate than with an Aeromonas hydrophila isolate. The role of extracellular polysaccharides and specific outer membrane proteins will have to be examined to reveal mechanisms of adherence and coaggregation employed by biofilm-forming F. johnsoniae-like strains.